Zawodowa wiedza Asaela (1 Hen. 8,1) i jej relacja do starożytnej Mezopotamii - Drawnel, Henryk (The Biblical Annals, 2015)
In 1 En. 8:1 one of the fallen Watchers, Asael, teaches humanity about the elaboration of metals, precious stones, and the use of minerals and dyes. In order to understand the reasons for the presentation of his professional skills, it seems necessary to analyze the cultural background of that Enochic tradition in the context of the Late Babylonian temple, with its large and skilled workforce used for the upkeep of cultic, economic and military activities. The Aramaic terminology in 1 En. 6:8 and 8:1 recovered from 4Q201 properly corresponds to what we now know about the functioning of the Babylonian artisans working for, and in cooperation with, the Late Babylonian temple.